Wavelet-probabilistic neural network-based intelligent system approach for spoken Hindi paired word classification. (16th August 2011) - Rajoriya, Dinesh Kumar; Anand, R.S.; Maheshwari, R.P.
This paper has proposed an idea to develop a speech controlled authenticated voice enabled system based on hybrid approach consisting of wavelet and probabilistic neural network (PNN) techniques. This hybrid approach is endeavoured for spoken paired word classification that is conceived of as an integral part of a speaker dependent intelligent system. Five hundred templates of spoken Hindi (Indian national language) paired word (SHPW) have been used for experimental validation of the proposed approach. The SHPW signal attributes are extracted by wavelet technique and classification/recognition has been examined with the help of PNN. Correct classification rate of proposed speaker dependent SHPW intelligent system is found to be 100% on considered database.